(3eONd Edi GdQjGVjGJ GdeGdjI h JWHjbGJgGs - (3dMSf YHO Gddg(B, (3HGThjIs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2011)
(3GdefWb GdQjGVj h CfhGY GdGaJQGVGJ , GdeLehYGJ h GdYdGbGJ h GdJWHjbGJ , GdeJJGdjGJ , GdQjGVjGJ GdeGdjI h GdaGFOI GdHSjWI , GdaGFOI GdeQcHI , GdHQeLI GdNWjIs
Keywords: (3GdQjGVjGJs; (3GdQjGVjGJ(B- (3GdeGdjI GdYGeIs